Like-layers resolution deficiency in structure function-based thermal test for multilayer semiconductor device and its potential cure by interface design - Xintian Gao; Junjie Wu; Yulin Chen; Haotian Huang; Yuan Zhu (Results in Engineering)
Multilayer thermal test has long been a challenge for many applications. In this work, we focus on the challenge it poses to the 3D architected semiconductor devices or integrated circuits (ICs). Structure function method (SFM) as an important commercialized measurement method for layered analysis of thermal resistance and thermal capacity, has been widely used and keeps attracting broad research interests from industry. It mimics the electrical R-C network to solve the thermal R-C network structure from the temperature response to a certain heat excitation. Here we report a like-layers resolution deficiency of SFM, which might be fatal for its use in 3D devices. 3D ICs have many like materials and layers repeating in the architecture. The mechanism of the deficiency is clarified by means of analytic derivation and simulations (both electrical and thermal). The cure we have found for this deficiency is a preliminary one. We use interface design to discern the like layers in the thermal test and it works under certain circumstance. In the end, the most used materials in 3D ICs including insulators (epoxy), semiconductors (Si, doped Si) and metals (Al, Ni, Cu, In, Ag) are estimated in real application scenarios. Some are found promising in solving the deficiency. The key novelty of present work is in identifying the resolution deficiency of SFM in like layers, which is crucial to 3D ICs. A preliminary solution through interface design is also provided.